Reduction of Retinal Thickness Ipsilateral to Hippocampal Sclerosis in Epilepsy - Xiong, Weixi; Lu, Lu; Chen, Qin; Xiao, Yingfeng; An, Dongmei; Sander, Josemir W.; Zhang, Ming; Zhou, Dong (Frontiers in Neurology, 2021)
Objectives: Reductions in the peripapillary retinal nerve fiber layer (pRNFL) have been reported in epilepsy, namely in drug-resistant people. Hippocampal sclerosis (HS) is the most frequent cause of drug-resistant epilepsy in tertiary care centers. We aimed to evaluate the likelihood and characteristic of RNFL loss in individuals with epilepsy having HS. Methods: Fifty-five adults diagnosed with unilateral HS (mean age of 25 years; 42 female) by magnetic resonance imaging were included in this observational cross-sectional study, 58 age-matched individuals with epilepsy with no detectable structural brain abnormality were included as non-HS, and 55 people without neurological diseases were included as healthy controls. pRNFL of both eyes was measured by optical coherence tomography (OCT). In each individual disease related information was recorded. Results: Among the 55 individuals with unilateral HS, one (1.82%) and ten (18.18%) had significant or borderline abnormal thinning of the pRNFL of the ipsilateral eye to the HS. The average pRNFL ipsilateral to the side of HS was significantly thinner than people with epilepsy non-HS (p = 0.013) and healthy controls (p = 0.000), especially in the inferior quadrants. Only age was significantly correlated with the average and inferior quadrant pRNFL thickness of the ipsilateral eye to the HS (R = −0.286, p = 0.035; R = −0.353, p = 0.008 respectively). Conclusion: These preliminary findings suggest that retinal abnormalities associated with HS may have a specific pattern. Further studies need to confirm this finding and to unravel the underlying mechanism.